Upaya Guru Pendidikan Agama Islam dan Budi Pekerti dalam Menanamkan Karakter Religius Siswa - Ermawan, Ega Dwi (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
What are the efforts of Islamic Religious Education Teachers in instilling Religious Character in Al-Huda Middle School Students in Kediri City? In instilling religious character in students, it becomes essential to strengthen and improve the morale of the nation's young generation, and teachers, as the spearhead of national education who play a significant role in carrying out the character building of students, are expected not to stop to innovate and be creative in creating strategies. Effective and efficient ways to improve the morals of students according to this national education goal. This study uses a qualitative approach and a descriptive type of research, taking the background at Al Huda Middle School, Kediri City. Data collection methods were carried out, including observation, interview, and documentation methods. Data analysis techniques use data reduction, display, and conclusion drawing (verification). Meanwhile, in testing the validity of the data using credibility (triangulation), dependability, and confirmability